2011
DOI: 10.4236/wja.2011.11001
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Prematurity among Neonates from HIV Positive Mothers in Cameroon

Abstract: Objective: Human immunodeficiency virus (HIV) infection is the most important chronic health condition among women in childbearing age in sub-Saharan Africa. There is sparse data about socio-economic factors in the context with adverse outcome in pregnancy. The objective of the study was to identify such factors for prematurity, low birth weight (LBW) and intrauterine growth retardation (IUGR) in infants born to HIV-positive women in Cameroon. Methods: The study was done in Yaoundé between December 2001 and No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Education also has been associated with increased use of antenatal care. 30,31 These women's literacy rate (91.9%) was greater than that of women in Cameroon (67.8% for women aged 15 years and older), with over half having some secondary and higher education. This higher educational level certainly contributes to these participant's use of and positive attitudes toward antenatal care.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Education also has been associated with increased use of antenatal care. 30,31 These women's literacy rate (91.9%) was greater than that of women in Cameroon (67.8% for women aged 15 years and older), with over half having some secondary and higher education. This higher educational level certainly contributes to these participant's use of and positive attitudes toward antenatal care.…”
Section: Discussionmentioning
confidence: 98%
“…Education also has been associated with increased use of antenatal care 30,31 . These women's literacy rate (91.9%) was greater than that of women in Cameroon (67.8% for women aged 15 years and older), with over half having some secondary and higher education.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that women with higher education were significantly more likely to attend prenatal care visit. 15 These potential determinants of poor growth other than HIV infection in mother have to be evaluated more precisely.…”
Section: Discussionmentioning
confidence: 99%